2006
DOI: 10.1111/j.1365-3083.2006.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Method for the Functional Analysis of Human Regulatory T Cells

Abstract: Naturally occurring regulatory T cells (Treg) suppress the activation of antigen‐responsive T cells in a cell contact‐dependent manner. In order to investigate the impact of soluble mediators and receptor–ligand interactions on the interplay between naive T cells and Treg, a reproducible suppressor cell assay which functions in the absence of additional feeder cells or antigen‐presenting cells is mandatory. Here, we describe such a method which is suited to study the modulation of responder T cell/Treg interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…If there is interaction between the two populations that may influence the behavior of Tregs, it would not be appropriate to characterize the behavior of Tregs in this way. However, many investigators followed this way of suppressive assay in which it is impossible to discriminate which population is actually proliferating in the coculture (Larkin et al, 2007;Oberg et al, 2006;Thornton and Shevach, 2000). In this way, as the stimulating signals are increased, Tregs begin to proliferate slightly, so-called, ''loss of anergy,'' along with the loss of suppressive activities, that is, vigorous proliferation in the coculture (Oberg et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…If there is interaction between the two populations that may influence the behavior of Tregs, it would not be appropriate to characterize the behavior of Tregs in this way. However, many investigators followed this way of suppressive assay in which it is impossible to discriminate which population is actually proliferating in the coculture (Larkin et al, 2007;Oberg et al, 2006;Thornton and Shevach, 2000). In this way, as the stimulating signals are increased, Tregs begin to proliferate slightly, so-called, ''loss of anergy,'' along with the loss of suppressive activities, that is, vigorous proliferation in the coculture (Oberg et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…This anergic state is closely linked with suppressive activity as abrogation of anergic state by TCR stimulation with high-dose IL-2 or CD28 ligation results in concomitant loss of suppressive activity (Oberg et al, 2006). Considering their low frequency in the periphery, it may be reasonable to raise the doubt how Tregs in anergic state can regulate the rapidly expanding effector cells properly in a contact-dependent manner when they are triggered.…”
Section: Introductionmentioning
confidence: 98%
“…The purity of the selected responder T cells and Tregs was .97%. The isolated T cells were cultured in serum-free X-VIVO-15 medium (Cambrex Bio Science, Verviers, Belgium) in an APC-free suppression assay as described (38). Briefly, 10 4 or 10 5 purified responder T cells, 2.5 3 10 3 or 5-7.5 3 10 4 purified autologous Tregs, or the coculture of these two subsets were stimulated with Activation/Expander Beads (Miltenyi Biotec).…”
Section: Isolation Of T Cell Populations and Cell Culturementioning
confidence: 99%
“…1A, T) or responder T cells (Fig. 1A, R) were affected by TLR2 ligands, each of the two T cell populations was isolated, separately pretreated for 24 h with the different TLR2 ligands, washed, and analyzed in the suppression assay (38). We observed that the Treg-mediated suppression of responder T cell proliferation (R/T) was completely abrogated after pretreatment of Tregs with a mixture of Pam 2 CSK4, FSL-1, and Pam 3 CSK4 in the majority (four of five) of experiments (representative experiment shown in Fig.…”
Section: Lipopeptides Abrogate the Suppressive Activity Of Human Tregsmentioning
confidence: 99%
“…CD4ϩ T cells were negatively isolated from fresh PBMCs by magnetic labeling of non-CD4ϩ T cells with a biotin-antibody cocktail and antibiotin MicroBeads (CD4ϩ T Cell Isolation Kit II; Miltenyi Biotec, Sunnyvale, CA) and then passing them over an LD magnetic bead column (Miltenyi Biotec). According to previously described techniques (17), the effluent preenriched CD4ϩ cells were labeled directly with CD25 Dynabeads using 75% of the recommended amount of beads and then separated using a magnetic particle concentrator (both from Dynal Biotech, New Hyde Park, NY). The supernatant contained the CD4ϩ,CD25Ϫ T cells.…”
Section: Isolation Of Cd4؉cd25-t Cells and Cd4؉cd25؉mentioning
confidence: 99%